Simulasi CFD Aliran Stratified Air-Udara pada Pipa Horisontal - Sukamta, Sukamta; Thoharudin, Thoharudin; Nugroho, Dedy Melianto (Semesta Teknika, 2018)
Two-phase flow can be found in industries, such as petroleum, electricity generation. In geothermal power plants, two-phase flow occurs from a mixture of water and steam which should be avoided in the piping system because it can cause equipment damage in the operating system. Therefore, an operator and engineer need a knowledge of flow patterns, phenomena and characteristics of the two-phase flow. One of the methods to predict the flow pattern is ud\sing the Computational Fluid Dynamic (CFD). This CFD simulation was modeled using Ansys Fluent 15.0 software to determine the changes of Stratified flow characteristics. The model used is Volume of Fluid (VOF). The fluid type is water and air. The variation of superficial water velocity JL of 0.025 m/s - 0.1 m/s while the superficial air velocity (JG) of 0.05 m/s - 1 m/s. The pipe used is an acrylic of 19 mm diameter and length of 1000 mm. The simulation results show that: (1). Stratified flow occurred for the low velocity of the liquid and gas phases. It was shown by the water and air are clearly separated. (2). Flow patterns are not stable, but it can change depending on the superficial velocity of gas and water. (3). The larger of JG causes the wave height because of Bernoulli’s effect so that it will make the stratified wavy or ripple flow pattern. (4). The frequency of stratified-wavy and ripple waves will tend to decrease when the JL increases, while the effect of JG is insignificant. Furthermore, it can be concluded that the speed of gas must be regulated so as not too large to the speed of water.